Geography Determinant Affecting Child Poverty in East Nusa Tenggara-Indonesia - Perseveranda, M.E. (International Journal of Psychosocial Rehabilitation, 2020)
Children are the population group that experience the most impact of poverty. The purpose of this study was to determine the factors that affect child poverty spatially in a specific location in the sub-district at Indonesia. The data was gained from integrated data from the Poor Handling Program, covering 306 districts in East Nusa Tenggara, Indonesia. The analysis used in this study is the Geographically Weighted Regression (GWR) method. The results showed that the burden of dependents, child labour, elderly workers, agricultural sector workers, non-agricultural sector workers, et cetera, have effected child poverty in East Nusa Tenggara. Therefore, it is strongly suggested that both central and regional governments, as policymakers, need to pay attention to aspects of spatial heterogeneity of the determinants of child poverty.